2019
DOI: 10.24036/spektrumpls.v2i1.103663
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Teachers in Managing Negative Emotion (Aggressive) of Early Childhood

Abstract: The current state of affairs in early childhood is the dominant type of aggressive emotion. Negative emotions (aggressive) can arise when the child is in school, so the teacher demands a role in managing the child's emotions. The purpose of writing this article is to find out the teacher's role in managing negative (aggressive) emotions in early childhood. The design of writing this article is a literature study. The teacher's role in managing negative emotions in children is to provide warmth to children, cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Individuals primarily in a state of emotional distress are expected to be very likely to engage in aggressive behavior (Warburton & Anderson, 2015). This is because emotions are situations in which an individual's physical change is manifested in the form of actions, behaviors, words, or expressions (Hazizah, 2019). Moreover, Sabourin et al also showed a lack of skills to solve problems have the ability to cause verbal aggression (Sabourin et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Individuals primarily in a state of emotional distress are expected to be very likely to engage in aggressive behavior (Warburton & Anderson, 2015). This is because emotions are situations in which an individual's physical change is manifested in the form of actions, behaviors, words, or expressions (Hazizah, 2019). Moreover, Sabourin et al also showed a lack of skills to solve problems have the ability to cause verbal aggression (Sabourin et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Hal ini membuat pemimpin dapat memfasilitasi kebutuhan dari anggota dengan memberdayakan (empowering), memberikan kebebasan dan tanggung jawab, serta memberikan kesempatan untuk menyuarakan pendapat (Schaufeli, 2021). Kepala sekolah berperan sebagai motor penggerak dan penentu kebijakan sekolah sehingga pemimpin dapat memberdayakan seluruh komponen dalam sekolah untuk dapat melaksanan proses belajar mengajar dengan baik (Hazizah, 2020). Dengan memberdayakan dan memberikan otonomi pada guru, pemimpin dapat mendorong terpenuhinya need of autonomy (Schaufeli, 2015).…”
Section: Pembahasanunclassified
“…Di akhir pemberlakuan PSBB di 31 April kemarin beberapa dareah sudah memastikan untuk kembali kepada kegiatan dan aktivitas masyarakat, seperti sediakala dengan memperhatikan protokol kesehatan dengan tetap membatasi jarak sosial. Kegiatan pendidikan pun juga akan dipersiapkan untuk kembali kepada sebelumnya belajar di sekolah (Nur Hazizah, 2020).…”
Section: Penarikan Kesimpulanunclassified